Pathogenicity of Salmonella Stanley isolate in commercial broiler chickens - R., Balqis; Bejo, Mohd Hair (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2018)
Salmonella Stanley (S. Stanley) is gram negative rods of the Enterobacteriaceae family commonly found in ducks, a reservoir of the bacteria. The potential risk for exposure to Salmonella via contaminated food rises with growth in consumption of meat and poultry products. The objectives of this study were to determine pathogenicity of S. Stanley isolate (UPM517) in chickens and to isolate the agent from the organs. The study showed that body weight of chickens in inoculated (A) and controlled (B) groups increased throughout the trial with no significant difference (p>0.05) between groups. No abnormal clinical signs were recorded in all groups, except on day 6 post inoculation (pi) one chick (1/8 or 12.5%) from mortality group A showed weakness and was found dead on the next day (day 7 pi). Necropsy revealed no significant findings in all groups, except splenomegaly in chicks from group A on day 4, 7 and 14 pi. Histologically the liver remained normal in all group of chickens. Salmonella was isolated from group A on day 1 pi from liver and caecal tonsils; on day 4 pi from liver, caecal tonsils and spleen; on day 7 pi from liver, spleen, caecal tonsils, cloacal swab; but on day 14 pi Salmonella was not isolated. No Salmonella was isolated from group B. Salmonella antibody titre declined in all groups throughout the trials with no significant difference (p>0.05) in the titre between groups. In conclusion, the S. Stanley isolate is pathogenic in commercial broiler chickens.